2021
DOI: 10.3390/genes12060937
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Phenotype Correlations in 208 Individuals with Coffin-Siris Syndrome

Abstract: Coffin-Siris syndrome (CSS, MIM 135900) is a multi-system intellectual disability syndrome characterized by classic dysmorphic features, developmental delays, and organ system anomalies. Genes in the BRG1(BRM)-associated factors (BAF, Brahma associated factor) complex have been shown to be causative, including ARID1A, ARID1B, ARID2, DPF2, SMARCA4, SMARCB1, SMARCC2, SMARCE1, SOX11, and SOX4. In order to describe more robust genotype-phenotype correlations, we collected data from 208 individuals from the CSS/BAF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 9 publications
1
47
0
7
Order By: Relevance
“…ARID1B gene are the most frequently mutated in CSS. The severity of physical abnormalities and intellectual defects varies from person to person (9)(10)(11)(12). We described two other patients with ARID2 gene variation, which is the rarest mutated in CSS.…”
Section: Arid2 Variants and Coffin-siris Syndromementioning
confidence: 98%
See 1 more Smart Citation
“…ARID1B gene are the most frequently mutated in CSS. The severity of physical abnormalities and intellectual defects varies from person to person (9)(10)(11)(12). We described two other patients with ARID2 gene variation, which is the rarest mutated in CSS.…”
Section: Arid2 Variants and Coffin-siris Syndromementioning
confidence: 98%
“…It plays an important role in cell proliferation, differentiation, development, and tumor suppression. ATP-dependent chromatin remodeling is a widely used mechanism (12,13). In mammals, 29 genes are predicted to encode protein complexes similar to yeast SWI2/SNF2.…”
Section: Arid2 Variants and Coffin-siris Syndromementioning
confidence: 99%
“…This multi-protein complex contains more than 15 subunits to activate gene expression through its capacity to remodel and remove nucleosomes at gene promoters [ 32 ]. Recently, mutations, translocations and deletions of the subunits in the SWI/SNF complex have been linked to a number of human diseases, such as cancer [ 33 ], different types of CSS [ 4 , 34 – 38 ] and NCBRS [ 15 ].
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that germline variants in SMARCB1 and SMARCA4 were involved in the CSS phenotype [137,138]. Germline PVs of SMARCB1 (n = 14, 7%) and SMARCA4 (n = 32, 15%) were also reported to be identified among 208 CSS patients [139].…”
Section: Molecular Geneticsmentioning
confidence: 99%